Implementation of Human Resource Management In Achieving The Vision of Jakarta Women Correctional Institution Class IIA - Winarsih, Retno; Oktavia Sapuding , Theresia (Dinasti International Journal of Digital Business Management, 2025)
This research aims to explain the implementation of Human Resource Management (HRM) in achieving the vision of the Jakarta Women Correctional Institution hereinafter referred to as LPP Jakarta, analyze support and hinder factors in the implementation of HRM, solutions used to overcome obstacles. The research method used is a qualitative descriptive approach. Data collection techniques with observation, interviews and documentation. The data analysis technique uses the Miles and Huberman interactive analysis model, namely data reduction, data presentation and drawing conclusions or verification. The results showed that: 1) The implementation of HRM in achieving the institutional vision was carried out through the stages of planning, recruitment, selection and placement, training and development, evaluation, and supervision. 2) The factors that support and hinder the implementation of HRM are well implemented, while discrepancies in planning and realization of the employees, mismatched educational backgrounds with job placement and a long bureaucracy are things that should be solved. 3) The solution to overcome obstacles are the 1st problem is to communicate intensively and continuously with the Jakarta Regional Office, for the 2nd problem is conducting “Internal Mutation” of the available staff by enhanced competence, 3rd the solution is implementing BKO (Bawah Kendali Operasi).